PERTANGGUNG JAWABAN KORPORASI DALAM TINDAK PIDANA PERSAINGAN USAHA DI INDONESIA - Sukrianto, Andi; Multiwijaya, Vience Ratna; Suar, Aprima (Ensiklopedia Sosial Review, 2024)
Abstract: Corporate accountability in business competition crimes in Indonesia is one of the important aspects in the effort to create a healthy and fair business competition climate. corporations or business entities can act as legal subjects that engage in anti-competitive actions detrimental to public interests, such as cartel monopoly practices or abuse of dominant positions. In the context of law in Indonesia, this business competition crime is regulated by various regulations, especially in. (Law No. 5 of 1999) This research method is used as a way to examine and analyze research problems, with the type of legal research used being normative legal research. descriptive in nature by adopting a regulatory approach (statute approach). In the Supreme Court Regulation Number 13 of 2016, Article 4, paragraph (1) states that corporations can be held accountable in accordance with corporate criminal provisions in the law governing corporations. If a corporation is proven to have committed an offense, both administrative and criminal sanctions can be imposed, with the aim of preventing anti-competitive behavior and protecting consumers and other business actors.Keywords: corporate accountability in criminal offenses.